Cremation report (Scottish Historical and Archaeological Internet Reports, 2005)
The cremated remains were found beside a broken cremation urn. The volume of the cremated remain was very small and the individual fragments were in very poor condition. Consequently, only a small percentage of the total could be identified and very few of the fragments provided any meaningful information. It cannot be stated with any certainty how many individuals were represented. Sex is unknown and there was no evidence of disease or cause of death.